0
$\begingroup$

I know that I can get the nth element of the following sequence

1   3   6  10  15  21

With the formula

(n * (n + 1)) / 2

where n is the nth number I want. How can I generalise the formula to get the nth element of the following sequences where by following sequences I mean

1 -> 1   3   6   10  15  21
2 -> 2   5   9   14  20
3 -> 4   8   13  19
4 -> 7   12  18
5 -> 11  17
6 -> 16
$\endgroup$
0
$\begingroup$

$$S_n=1+2+4+7+11+16+\cdots+t_n$$

$$S_n=\cdots\cdots\cdots1+2+4+7+11+16+\cdots+t_n$$

$$S_n-S_n=1+(2-1)+(4-2)+(7-4)+(11-7)+\text{ up to }n-1\text{ terms}-t_n$$

$$\implies t_n=1+\dfrac{(n-1)(1+n-1)}2$$

Now the $r(1\le r\le6)$th row has $6+1-r$ terms starting with $1+\dfrac{r(r-1)}2$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.